2012
DOI: 10.1002/jbio.201100108
|View full text |Cite
|
Sign up to set email alerts
|

The utility of far‐infrared illumination in oxygenation dynamics as measured with near‐infrared spectroscopy

Abstract: Near-infrared spectroscopy (NIRS) is a noninvasive method for measuring the oxygenation in muscle and other tissues in vivo. For quantitative NIRS measurement of oxygenation dynamics, the vessel-occlusion test was usually applied as physiological intervention. There are several drawbacks of the vessel-occlusion method that include skin contact, uncomfortable and microcirculation block of patients. Thus, we propose the far-infrared (FIR) illumination as a new physiological intervention method in this paper. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In our previous study, we showed that a relationship exists between AOTs and FIR illumination tests for detecting tissue oxygenation through NIRS assessment. The results of that study indicated that FIR illumination tests might be a suitable physiological intervention for replacing AOTs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we showed that a relationship exists between AOTs and FIR illumination tests for detecting tissue oxygenation through NIRS assessment. The results of that study indicated that FIR illumination tests might be a suitable physiological intervention for replacing AOTs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…NIRS has been proposed as a real‐time noninvasive system for monitoring regional microcirculation and is based on different absorption and scattering coefficients of more than two wavelengths. Our study published in 2012 revealed a linear correlation in oxygenation dynamic signals between NIRS and an arterial occlusion test [13], implying that NIRS can be a tool for clinical diagnosis. We published a study comparing 44 healthy participants with 35 patients with sepsis in an ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study from 2012 showed a linear correlation of oxygenation dynamic signals between FIR illumination and an arterial‐occlusion test, implying that FIR illumination can be applied in clinical diagnoses . Subsequently, we determined that FIR hemodynamics vary between sexes, with females experiencing smaller increases in HbO 2 than males do.…”
Section: Introductionmentioning
confidence: 99%